Modeling volcanic ash resuspension - Application to the 14-18 October 2011 outbreak episode in central Patagonia, Argentina - Folch Duran, Arnau (2014)
Volcanic fallout deposits from the June 2011 Cordón Caulle eruption on central Patagonia were remobilized in several occasions months after their emplacement. In particular, during 14-18 October 2011, an intense outbreak episode generated widespread volcanic clouds that were dispersed across Argentina, causing multiple impacts in the environment, affecting the air quality and disrupting airports. Fine ash particles in volcanic fallout deposits can be resuspended under favorable meteorological conditions, particularly during strong wind episodes in arid environments with low soil moisture and poor vegetation coverage. As opposed to eruption-formed ash clouds, modeling of resuspension-formed ash clouds has received little attention. In consequence, there are no emission schemes specially developed and calibrated for resuspended volcanic ash, and few operational products exists to model and forecast the formation and dispersal of resuspension ash clouds. Here we implement three dust emission schemes of increasing complexity in the FALL3D tephra dispersal model and use the 14-18 October 2011 outbreak episode as a model test case. We calibrate the emission schemes and validate the results of the coupled WRF-ARW (Weather Research and Forecasting - Advanced Research WRF)/FALL3D modeling system using satellite imagery and measurements of visibility (a quantity related to total suspended particle concentration at the surface) and particulate matter (PM10) concentration at several meteorological and air quality stations located at Argentina and Uruguay. Our final goal is to test the capability of the modeling system to become, in the near future, an operational forecast product for volcanic ash resuspension events.